2020
DOI: 10.1109/access.2020.3019180
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Analytical Approach Using Rough Set and Genetic Algorithm of a Stable Sensorless Induction Motor Drives in the Regenerating Mode

Abstract: A novel approach for optimized feedback gains of a stable sensorless induction motor (IM) drives at low speeds in the regenerating mode is presented. The proposed approach depends on the rough set (RS) and genetic algorithm (GA) in a cascading construction. The RS is used to obtain the most dominant machine parameters that affect the stability of the sensorless IM drive at very low speeds in the regenerating mode. The parameter's values are randomly selected to investigate their influence on the stability. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Hence it is suggested to utilize AI to recognize, estimate and control nonlinear functional systems. The common AI strategies include artificial neural networks [ 27 , 28 , 42 , 78 ], fuzzy logic [ 50 , [79] , [80] , [81] ] and genetic algorithms [ 82 , 83 ]. They own the features of protection against input harmonic fluctuations and hardness to variations of parameter.…”
Section: Machine Model-based Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence it is suggested to utilize AI to recognize, estimate and control nonlinear functional systems. The common AI strategies include artificial neural networks [ 27 , 28 , 42 , 78 ], fuzzy logic [ 50 , [79] , [80] , [81] ] and genetic algorithms [ 82 , 83 ]. They own the features of protection against input harmonic fluctuations and hardness to variations of parameter.…”
Section: Machine Model-based Methodsmentioning
confidence: 99%
“…This design uses a two-dimensional phase plane and general rules. An off-line genetic algorithm (GA) system is used to fine-tune the input and output scale factors of the fuzzy PI controllers (K1, K2, K3) to reduce the ω r , i qs , and i ds error [ 5 , 30 , [81] , [82] , [83] , [93] , [94] , [95] , [96] ]. The integral with time of absolute error (ITAE) fitness function has been chosen to assess the individuals of each generation.…”
Section: Machine Model-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rough sets theory [103] revolves around the notion of data discernibility. The data mining aspects of rough sets theory is a non-statistical, mathematical tool for dealing with ambiguous and imprecise data [104]. A recent bibliometric analysis of rough sets theory conducted by Yu et al [105] demonstrated that attribute reduction was the focal point of rough set research in both theoretical and application domains.…”
Section: B the Rough Set Fundamentalsmentioning
confidence: 99%